A REVIEW ON THE CONTEXTUAL TEACHING AND LEARNING PROCESS USING PROCEDURAL TEXT WRITING - Sulviana Sulviana (Bajang Institute, 2022)
The purpose of this study was to review the use of procedural text in writing in the contextual learning and teaching process in high school English class to develop students' ability in writing procedural text. The method of this research was descriptive qualitative. Data collection techniques were obtained through teacher and students observation. The results showed that the implementation of the Contextual Teaching and Learning model using writing text procedure increased teacher and student activities. The implementation of procedural text in English writing class showed the students to be more interested to the learning process. Thus, contextual procedural texts in teaching language class, particularly to English writing gave better result in improving students’ interest in writing English material